FAKTOR-FAKTOR YANG MEMPENGARUHI KONSERVATISME AKUNTANSI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014-2016 - Nobita Sugiarto; Ida Nurhayati (Faculty of Economic and Business Universitas STIKUBANK, 2017)
This study examines the effects of institutional ownership structures, managerial ownership structures, public ownership structures, growth opportunities,debt convenant (leverage), tax and political costs, litigation risk to accounting conservatism. The research was conducted at the Indonesian Stock Exchange by using a go public manufacturing company as the unit of analysis. The sampling method used purposive sampling with the observation period from 2014-2016. Relationship and between variable is described by using multiple regression analysis. The results showes that the institutional ownership structures had no significant effect on accounting conservatism,managerial ownership structures had no significant effect on accounting conservatism, public ownership structures had no significant effect on accounting conservatism, growth opportunities has negative no significant effect on accounting conservatism, Debt Convenant (leverage) has negative effect on accounting conservatism, tax and political costs has positive effect on accounting Conservatism, litigation risk has negative effect on accounting conservatism Keyword: institutional ownership structures, managerial ownership structures, public ownership structures, growth opportunities,debt convenant (leverage), tax and political costs, litigation risk and accounting conservatism.